Effect of surface roughness on the magnetic interaction between micron-sized ferromagnetic particles: Finite element method calculations. (May 2017) - Vereda, Fernando; de Vicente, Juan; Hidalgo-Alvarez, Roque
We report a finite element method study on the effect of surface roughness on the field-induced magnetization of micrometric iron particles and on the interparticle magnetostatic forces between them. Calculations were carried out for two-dimensional geometries in which particles were modelled as discs. Roughness was introduced as semicircular protrusions or as triangular- or square-wave profiles. Interestingly, we found that increasing amplitudes of the triangular- or square-wave profiles facilitated the magnetization of the particles, resulting in larger interparticle forces at fields below saturation. The effect of the semicircular protrusions and of the spatial frequency of the wave profiles was comparatively small, suggesting that in real systems the effect of particle roughness on magnetic properties may depend on the specific surface morphology. The permeability of the particles also influenced the extent to which roughness facilitated the magnetization process: a larger permeability resulted in larger differences between the magnetization curves of the smooth and the rough particles. Results are relevant to magnetorheological fluids, since we show that surface roughness can affect the magnetic interactions between particles.